Homocarbaporphyrinoids: The m‐o‐m and p‐o‐p Terphenyl Embedded Expanded Porphyrin Analogues and Their RhI Complexes. Issue 18 (8th March 2019) - Adinarayana, B.; Das, Mainak; Suresh, Cherumuttathu H.; Srinivasan, A.
Abstract: Stable homocarbaporphyrinoids were successfully synthesized by incorporating the m‐o‐m and p‐o‐p terphenyl units into the porphyrin core. The distinct bonding modes of terphenyl in the macrocycle generated two structural isomers with two and four carbon atoms in the macrocyclic environment. The core was utilized to stabilize the Rh I ion. The spectral and structural analyses revealed that the restricted ( m‐o‐m ) and allowed ( p‐o‐p ) conjugation in the macrocyclic core provide overall non‐aromatic characteristics both to the free bases and their complexes. Abstract : New porphyrinoids : After the core‐modified and aza‐homoporphyrins, carba‐homoporphyrins were successfully achieved by introducing the m‐o‐m and p‐o‐p ‐terphenyl units into the core. The di‐ and tetracarba‐homoporphyrins are structural isomers and form complex with Rh I ions. The structural analyses revealed non‐aromaticity, which is mainly due to the restricted conjugation at the m ‐phenylene unit and the decreased planarity for the p ‐isomer.